Vaginal Royal Jelly for Vulvovaginal Candidiasis Treatment: A Randomized Clinical Trial - Maryam Ramazany Chaleshtori; Mahmoodreza Madadian; Azadeh Akbari Sane; Farahnaz Farzaneh; Vida Kazemi; Fatemeh Montazer; Susan Sarhadi; Maryam Taghavi Shirazi; Shahla Mirgaloybayat (Advanced Biomedical Research)
Background: Vulvovaginal Candidiasis (VVC) is a prevalent and complex health issue in women. With the rising resistance to synthetic antifungal medications, there is a growing emphasis on exploring natural remedies that minimize disruption to the normal vaginal flora. The goal of this study is to evaluate the efficacy of vaginal Royal Jelly (RJ) compared with clotrimazole for VVC treatment. Materials and Methods: This single-blind randomized clinical trial was conducted from 2020 to 2022 at Iran University of Medical Sciences hospitals, involving a total of 90 patients diagnosed with vaginal candidiasis. Positive vaginal culture individuals were randomly allocated to receive either vaginal 1000 mg RJ soft gel capsules or (2%) Clotrimazole cream (45 participants per group). Clinical signs, symptoms, and laboratory tests were statistically compared at baseline and ten days post-treatment. The data were analyzed using the independent t-tests, Mann-Whitney, Chi-square, and Wilcoxon tests through SPSS version 22. Results: After 10 days of treatment, both groups demonstrated a significant decrease in Candida culture results (P < 0.001). RJ also positively impacted vaginal symptoms such as itching, discharge, and burning. Moreover, most patients in both groups became asymptomatic post-treatment. Conclusions: The present study points out the therapeutic effects of vaginal RJ, a novel natural drug for improving VVC.